Psychometric Properties of the Authoritarian Attitude Scale in a Sample of Chilean Adolescent Students - Ignacio Norambuena-Paredes; Karina Polanco-Levicán; Gustavo Troncoso-Tejada; Guillermo Davinson-Pacheco; Julio Tereucán-Angulo; José Luis Gálvez-Nieto; José Sepúlveda-Maldonado; Cristina Tavera-Cuellar; Adriana Bertoldi Carretto de Castro; Ítalo Trizano-Hermosilla (Behavioral Sciences, 2025)
This study aims to evaluate the psychometric properties of the Authoritarian Attitude Scale in a sample of high school students from Chile. A total of 775 students (46.5% men; 53.5% women), with an average age of 15.99 years (Sd = 1.32), participated through non-probabilistic convenience sampling in 11 schools. Confirmatory factor analysis supported a three-factor structure with correlated factors and adequate fit indices. Criterion validity revealed positive and significant correlations with the violent behaviour dimension of the antisocial and delinquent behaviour scale. The factorial invariance analysis confirmed configural, weak, strong, and strict equivalence by gender, age and ethnicity, demonstrating model stability. The adoption of the Authoritarian Attitude Scale among Chilean adolescents provides a valid, culturally relevant tool for assessing authoritarian tendencies and understanding psychosocial dynamics in the educational context. The findings offer initial evidence of the scale’s reliability and validity.